111Indium Labelling of Recombinant Activated Coagulation Factor VII: In Vitro and Preliminary In Vivo Studies in Healthy Rats. (13th February 2012) - Nalla, Amarnadh; Buch, Inge; Sigvardt, Maibritt; Bodholdt, Rasmus Poul; Kjaer, Andreas; Hesse, Birger
Abstract : The aim of this study is to investigate whether 111 Indium-labelled recombinant FVIIa (rFVIIa) could be a potential radiopharmaceutical for localization of bleeding sources. DTPA-conjugated rFVIIa was radiolabelled with 111 In chloride. In vitro binding efficiency of 111 In-DTPA-rFVIIa to F1A2-Mab-sepharose was 99% in buffer, while it was 88–82% in serum. The binding efficiency of 111 In-DTPA-rFVIIa to TF (1–209)-sepharose was 48% in buffer whereas 39%–36% in serum, respectively. In vivo experiment was conducted in healthy rats, and gamma camera images were taken immediately after iv. administration of 1.6–1.8 MBq 111 In-DTPA-rFVIIa up to 120–130 min. Five min after administration of 111 In-DTPA-rFVIIa, percentage of 111 In activity was 6.0% in the cardiac region and 24.5% in the liver region. After 2 hours activity was decreased to 3.3% in heart while it had increased to 42.0% in the liver. The 111 In-DTPA-rFVIIa might be a potential radiopharmaceutical for visualisation of tissues with significant TF expression such as acute bleeding lesions in the gastrointestinal tract.